Why do ethnic Chinese in the Netherlands underutilize mental health care services? Evidence from a qualitative study. (June 2015) - Liu, Cha-Hsuan; Meeuwesen, Ludwien; van Wesel, Floryt; Ingleby, David
Chinese immigrants in the Netherlands are less likely than other ethnic groups to utilize mainstream mental health care services. This study investigated the experiences of Chinese with mental health problems, to inform measures to make services more responsive to the needs of this group. Qualitative methods of analysis were applied to interview data in order to explore ways of finding help, barriers to accessing mainstream mental health care, experiences in care, factors jeopardizing the quality of care, and views on mental health services among Chinese migrants in the Netherlands. Rather than recruiting individuals with mental health problems, an indirect method was used in which ethnic Chinese participants were invited to tell us about one or more Chinese individuals in their social environment whom they regarded as having (had) mental health problems ( ). Although most Chinese regarded mainstream Dutch care as the appropriate resource for dealing with mental health problems, many barriers to access and threats to care quality were reported. In contrast to the widely accepted view that cultural differences in health beliefs underlie the low utilization of mental health services by Chinese in the West, the main obstacles identified in this study concerned practical issues such as communication problems and lack of knowledge of the health system. Respondents also described concerns about entitlement to care and discrimination (actual or anticipated). Measures suggested by respondents for improving care included increased use of interpreters and cultural mediators, encouraging migrants to increase their language proficiency, and better dissemination of information about the health system. The article concludes with a discussion of the policy implications of these findings.